Co-treatment of gypsum sludge and Pb/Zn smelting slag for the solidification of sludge containing arsenic and heavy metals. (1st October 2016) - Li, Yuan-Cheng; Min, Xiao-Bo; Chai, Li-Yuan; Shi, Mei-Qing; Tang, Chong-Jian; Wang, Qing-Wei; Liang, Yan-jie; Lei, Jie; Liyang, Wen-Jun
Abstract: Wastewater treatment sludge from a primary lead-zinc smelter is characterized as hazardous waste and requires treatment prior to disposal due to its significant arsenic and heavy metals contents. This study presents a method for the stabilization of arsenic sludge that uses a slag based curing agent composed of smelting slag, cement clinker and limestone. The Unconfined Compressive Strength (UCS) test, the China Standard Leaching Test (CSLT), and the Toxicity Characteristic Leaching Procedures (TCLP) were used to physically and chemically characterize the solidified sludge. The binder ratio was determined according to the UCS and optimal experiments, and the optimal mass ratio of m (smelting slag): m (cement clinker): m (gypsum sludge): m (limestone) was 70:13:12:5. When the binder was mixed with arsenic sludge using a mass ratio of 1:1 and then maintained at 25 °C for 28 d, the UCS reached 9.30 MPa. The results indicated that the leached arsenic content was always less than 5 mg/L, which is a safe level, and does not contribute to recontamination of the environment. The arsenic sludge from the Zn/Pb metallurgy plant can be blended with cement clinker and smelting slag materials for manufacturing bricks and can be recycled as construction materials. Graphical abstract: Highlights: Arsenic sludge was solidified with nonferrous industrial residue. The utilization ratio of waste is high, and the amount of cement clinker is low. Solidified samples can be potentially used in the common industrial construction.